Submucosal Lifting Agent ORISE Gel Remnants Histopathologically Mimic Mucin and Malignancy: A Case Series. (11th September 2019) - Cypher, Luke; Sun, Shaoli; Forster, Erin; Hoffman, Brenda; Lewin, David
Abstract: Introduction: There were an estimated 18.1 million new cancer cases in 2018, with colon cancer being the third most common worldwide. Colon cancer development is an accumulation of mutations resulting in normal epithelial cells transforming into adenomas and then adenocarcinomas. In certain scenarios, endoscopic interventions have gained considerable momentum over invasive surgery as an alternative to manage early gastrointestinal lesions. New techniques such as endoscopic mucosal resection (EMR) and endoscopic submucosal dissection allow for removal of large, flat sessile polyps. Successful EMR is dependent on expanding the submucosal space to create adequate lift of the polyp to facilitate tissue capture and to avoid perforation and excess bleeding. ORISE gel (Boston Scientific) is a submucosal lifting agent currently in use in the United States. Methods: We present three cases of gastrointestinal specimens obtained using ORISE gel. Histological analysis with hematoxylin and eosin revealed submucosal amorphous deposits that appeared to be mucin. Due to the concern for malignancy, additional stains were performed, including periodic acid–Schiff with diastase digestion (DPAS) to identify mucin. DPAS staining for mucin was negative, indicating the mucinous-appearing amorphous material seen on hematoxylin and eosin staining was not mucin but a likely remnant ORISE gel used during EMR. Additional immunohistochemical stains for epithelial cells (cytokeratin AE1/AE3) were also performed to exclude the presence of infiltrating tumor cells. Conclusion: These three cautionary cases reveal the importance of good communication between endoscopists and pathology. In an effort to avoid overdiagnosis and/or the usage of unnecessary additional stains, pathologists should be alerted of ORISE gel usage.